Linguocultural peculiarities of Sh. Ualikhanov’s works as reflection of national and historical flavor (Eurasian Journal of Philology Science and Education, 2021)
This article describes the results of the analysis of the works of Sh. Ualikhanov, the first Kazakh scientist, ethnographer, folklorist, educator, who transferred the knowledge about the Kazakh people, their traditions, religion, government, legends, presented the diversity of flora and fauna of Kazakhstan, the originality of the landscape, way of life and culture of the Kazakh people. The scientist’s works greatly contributed to the study of the history, culture and literature of the peoples of Central Asia. His creative heritage goes beyond national identity and can be of great interest for the world science in the context of intercultural communication and intercultural education. The article presents various types of Kazakh national realia, as well as their linguocultural features in the works of Sh. Ualikhanov. Realias are words and phrases that name objects, phenomena, objects characteristic of the life, everyday life, culture, social and historical development of one people and unfamiliar or alien to another people, expressing national and (or) temporary flavor, which do not have exact matches in another language. A particular attention is focused on conveying features of the historical era, culture, national character.